Validity of the Construct and Reliability of the Indonesian Version of the Cancer Fatigue Scale (CFS) Instrument in Measuring Fatigue in Cancer Patients - Ahmad Fadhlur Rahman; Dewi Gayatri; Giur Hargiana; Yati Afianti; Retno Setiowati (GLOBAL HEALTH SCIENCE GROUP, 2026)
Cancer-related fatigue is one of the most frequent symptoms and has a significant impact on the quality of life of cancer patients. Accurate fatigue measurements require instruments that are valid and reliable, and appropriate to the cultural and linguistic context. Therefore, it is necessary to test the validity of the construct and reliability of the Indonesian version of the Cancer Fatigue Scale (CFS) before it is widely used. This study aims to test the validity of the construct and reliability of the Indonesian version of the Cancer Fatigue Scale (CFS) instrument in measuring fatigue in cancer patients. This study is an analytical descriptive research using a Cross Sectional design. This research was conducted at Darmais Cancer Hospital (RSKD). The number of samples was 220 people, with a sampling technique, namely purposive sampling. The instrument used in this study was the Cancer Fatigue Scale (CFS) as the core questionnaire. The data was analaysed to test realibility and validity of instruments CFS. The results showed that all Indonesian version of CFS items had a total item–correlation value above the minimum acceptable limit (r > 0.30), indicating adequate construct validity. The reliability test showed Cronbach's alpha value of 0.824, which indicated good internal consistency. The Indonesian version of the Cancer Fatigue Scale has been proven to have good construct validity and reliability, making it suitable for use as an instrument for measuring fatigue in cancer patients in oncology nursing research and practice.